Robotic arm - Misk Sawallha; Ansam Darweesh (My University, 2022)
Since the creation of humans, people have been seeking ways to make their tasks easier and faster. From the invention of the wheel to the Webb Space Telescope, technological advancements have played a significant role in this pursuit. The rise of the robot industry has been particularly influential in this regard. Robots have become a major industry and are used in various aspects of life. However, most robots are programmed to perform a specific task and are unable to respond to real-time human inputs. To solve this problem, our project proposes a robotic arm controlled by a person through a glove equipped with sensors. The robotic arm, powered by motors, mimics the movements of a human arm. All of this is managed by a software system that communicates with the sensors on the glove. This project would replace the need for a human to perform dangerous tasks, such as chemical experiments, laser science, or x-ray centers, providing protection from hazardous environments.